Implementation of Educational Quality Assurance and Control at MTs As'adiyah, Female Section, Sengkang, Wajo Regency - Usman Pateha; Muhammad Hasibuddin (Global Education Journal, 2026)
In the Indonesian context, the quality of education is a primary focus of national development, as stipulated in Law Number 20 of 2003 concerning the National Education System, which affirms that education functions to develop abilities and shape the character and civilization of a dignified nation. This research aims to deeply analyze the process of educational quality assurance and quality control at MTs As’adiyah for Girls, focusing on the implementation of the Internal Quality Assurance System (SPMI) and the mechanisms of academic and non-academic quality control. This study employs a descriptive qualitative approach, collecting data through in-depth interviews, participatory observations, and document analysis. The main informants include the principal, vice principal for curriculum affairs, teachers, administrative staff, and education supervisors from the Ministry of Religious Affairs of Wajo Regency. The findings reveal that the quality assurance process at MTs As’adiyah is systematically carried out through the PPEPP cycle (Determination, Implementation, Evaluation, Control, and Improvement) as mandated by the Indonesian Ministry of Education Regulation No. 28/2016. In the context of quality control, the school applies a continuous improvement model inspired by Total Quality Management (TQM) and the Deming Cycle (Plan–Do–Check–Act) but adapted to the pesantren culture emphasizing spirituality and moral integrity.